2011
DOI: 10.5194/acp-11-7747-2011
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron beams above thunderclouds

Abstract: Abstract. Non-luminous relativistic electron beams above thunderclouds have been detected by the radio signals of low frequency ∼40-400 kHz which they radiate. The electron beams occur ∼2-9 ms after positive cloud-to-ground lightning discharges at heights between ∼22-72 km above thunderclouds. Intense positive lightning discharges can also cause sprites which occur either above or prior to the electron beam. One electron beam was detected without any luminous sprite which suggests that electron beams may also … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…However, it can again be said that the observations of lightning associated with TGFs are not consistent with this explanation. Moreover, is not clear if such energetic electron beams, with extremely large fluences ejected into space, are the only explanation for the observed radio emission, as lightning flashes as complex as those that typically produce sprites (Shao and Krehbiel 1996;Lu et al 2009) commonly produce impulsive LF radio pulses of the type reported by Füllekrug et al (2010Füllekrug et al ( , 2011 through ordinary lightning processes.…”
Section: Rrea Sprites and Other Tlesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can again be said that the observations of lightning associated with TGFs are not consistent with this explanation. Moreover, is not clear if such energetic electron beams, with extremely large fluences ejected into space, are the only explanation for the observed radio emission, as lightning flashes as complex as those that typically produce sprites (Shao and Krehbiel 1996;Lu et al 2009) commonly produce impulsive LF radio pulses of the type reported by Füllekrug et al (2010Füllekrug et al ( , 2011 through ordinary lightning processes.…”
Section: Rrea Sprites and Other Tlesmentioning
confidence: 99%
“…Nevertheless, recent work by Galper and Koldashov (2007) has revisited this topic, modeling high altitude runaway electron beams. Füllekrug et al (2010Füllekrug et al ( , 2011 have claimed to have identified RF signatures of energetic electron beams due to high altitude RREA in association with sprites. However, it can again be said that the observations of lightning associated with TGFs are not consistent with this explanation.…”
Section: Rrea Sprites and Other Tlesmentioning
confidence: 99%
“…During lightning discharges, wideband electromagnetic signals (DC-UHF, ultrahigh frequency) are emitted. Lightning location systems (LLSs) operating at different frequency ranges were developed gradually to study the diverse electromagnetic phenomena, such as red sprites (e.g., Cummer & Füllekrug, 2001), blue jets (e.g., Cummer et al, 2009), electron beams (e.g., Füllekrug, 2011), and other related interesting events (e.g., Gemelos et al, 2009;Qin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was proposed that the lightning electromagnetic field can accelerate electrons above thunderclouds from the cosmic ray layer upwards to produce avalanching relativistic electron beams (Roussel-Dupré et al 1998, Roussel-Dupré andGurevich 1996). Experimental evidence for such electron beams was reported by remote sensing with low frequency radio waves (Füllekrug et al 2011b(Füllekrug et al , 2010. The lightning electromagnetic field also causes Joule heating above thunderclouds which results in electrical breakdown of air such that sprite streamers develop (Pasko 2010).…”
Section: Introductionmentioning
confidence: 99%